Methodological flaws in corpus-based studies on Malaysian ESL textbooks - Zarifi, Abdolvahed; Mukundan, Jayakaran; Kalajahi, Seyed Ali Rezvani (Australian International Academic Centre, 2014)
With the increasing interest among the pedagogy researchers in the use of corpus linguistics methodologies to study textbooks, there has emerged a similar enthusiasm among the materials developers to draw on empirical findings in the development of the state-of-the-art curricula and syllabi. In order for these research findings to have their impact felt in language pedagogy, the researchers should, however, follow the well-established principles of the methodology. In an attempt to investigate the extent to which the researchers abide by these standards, the current paper reviews a number of corpus-based studies carried out on the ELT textbooks in Malaysia. It was specifically intended to shed light on the possible methodological flaws committed by the researchers. The study, it is the hope of the researchers, could provide some guidelines for the researchers to carry out further corpus-based studies on EFL/ESL instructional materials as well.